Clinical Factors Associated with the Diagnosis of Granulomatosis with Polyangiitis. (March 2017) - Eren, Erdem; Kalkan, Toygar; Arslanoğlu, Seçil; Özmen, Mustafa; Önal, Kazım; Tarhan, Emine Figen; Akar, Servet
Objective: To determine the predictive value of nasal endoscopic findings and symptoms in the diagnosis of granulomatosis with polyangiitis (GPA). Study Design: A cross-sectional study. Setting: A tertiary university hospital. Subjects and Methods: A total of 116 adults were enrolled in the study: 19 patients with GPA, 29 patients with other rheumatic diseases, and 68 healthy volunteers. All patients were examined with a flexible endoscope, and nasal endoscopic images were recorded and evaluated blindly. The medical history of each patient was taken by a physician blinded to the patient's diagnosis. Results: Univariate analysis indicated a statistically significant difference in rhinorrhea ( P = .002), postnasal drip ( P = .015), epistaxis ( P < .001), and saddle nose ( P = .017). However, binary logistic regression analysis demonstrated that only history of epistaxis ( P = .012; odds ratio, 5.6) was statistically significant in predicting GPA. Univariate analysis showed a statistically significant difference in nasal secretion ( P = .028), nasal septal perforation ( P < .017), nasal crusting ( P < .001), nasal adhesion ( P < .001), nasal granuloma ( P = .017), and hemorrhagic fragile nasal mucosa ( P < .001). A binary logistic regression analysis demonstrated that only hemorrhagic fragile nasal mucosa ( P < .001; odds ratio, 52.9) was a statistically significant predictor of GPA. Conclusions: Given the results of this study, we believe that hemorrhagic fragile nasal mucosa and history of recurrent epistaxis may put patients at risk for GPA and should be investigated accordingly.